Isolated Bilateral Complete Cryptophthalmos - Farooqui, Javed Hussain; Hà, Thanh Huy Thiên; Gomaa, Ahmed (Nepalese Journal of Ophthalmology, 2017)
Cryptophthalmos is a rare congenital anomaly, characterized by extension of the skin continuously from forehead onto the cheeks and covering eyeballs. Although cryptophthalmos, as a part of Fraser syndrome, has been reported many times, isolated cryptophthalmos without systemic associations is very rare. We present a 6-month- old child with isolated bilateral complete cryptophthalmos, which to the best of our knowledge, is the first case of cryptophthalmos being reported from Vietnam.